Digital Divide and Effectiveness of E-learning during COVID-19 Pandemic - Dahal, Aastha; Mishra, Binay (Samriddhi Journal of Development Studies, 2024)
The COVID-19-induced halt in in-person classes in Nepal led to a paradigm shift in the educational process as the classes began to run through online platforms. However, literature suggests that not everyone could fully benefit from it, especially in developing countries like Nepal. In this regard, the paper investigates the digital divide in e-learning amongst secondary-level students of community and institutional schools and the extent to which e-learning is effective for them. The assessment captures differences in terms of the availability of hardware elements, approach to software elements, and adaptation by meatware (human) elements. A comparative study, using a questionnaire as a primary tool for data collection, was carried out on three community (public) schools and three institutional (private) schools in Kathmandu. The study finds that students from both types of schools do not have adequate access to e-learning. Nonetheless, in consistency with the established knowledge,it is found that the general tendency of students of institutional schools being marginally better off in terms of access to relevant devices, and diverse e-learning platforms. Moreover, they demonstrated greater adaptability to e-learning platforms compared to their community schools’ counterparts.